Evaluación preliminar del riesgo de estructuras en construcción mixtas de uso residencial, ubicadas en la intersección de las calles Cuenca y Esmeralda - Zambrano Sánchez, Xavier Antonio (2025)
This thesis aims to conduct an initial analysis of the risks faced by structures under construction in this specific area of Guayaquil, characterized by rapid urban growth and a mix of residential and commercial uses. The study focuses on evaluating the factors that influence the safety of these constructions, such as the type of materials used, soil conditions, expected loads, and the stability of the infrastructure. To this end, a detailed review of local construction regulations is carried out, the characteristics of the construction sites are inspected, and the hazards associated with the location are analyzed, such as proximity to high seismic risk areas, flooding, or potential landslides. Additionally, tools and methods for structural risk assessment are incorporated, based on vulnerability analysis and qualitative and quantitative methods............